Aktivasi Gereja Online Peluang Pembangunan Gereja Online HKBP Maranatha Cilegon - Manalu, Musdodi Frans Jaswin (Universitas Sanata Dharma, 2024)
This research aims to analyse the establishment of online churches as an alternative medium for worship during the COVID-19 pandemic, focusing on the approach of religious people in the digital era. The case study focused on the Huria Kristen Batak Protestan (HKBP) Church of Cilegon, which had difficulty accessing a physical church in Cilegon. The COVID-19 pandemic is the right momentum to realise online worship, considering that most churches have been running online worship for approximately the last two years. The resulting recommendation is to establish an online church involving the entire HKBP Cilegon congregation with officially recognised and registered leadership. If HKBP rules and regulations can allow this, it will be the first online church in Indonesia. This research uses qualitative research methods on online news sources and supporting literature. The results of this research are expected to contribute positively to overcoming the difficulty of accessing physical churches during the pandemic and help mediate inter-religious tensions. The limitation of this research is the focus on HKBP Cilegon as a case study, and an in-depth research on the impact of online churches in the wider Indonesian society would be an interesting further study. Abstrak Pembatasan mobilitas selama pandemi menyebabkan masyarakat melakukan aktivitas secara online, termasuk beribadah. Gereja online menjadi salah satu alternatif yang memudahkan masyarakat untuk tetap menjalankan ibadah. Penelitian ini bertujuan untuk menganalisis pendirian Gereja online sebagai media alternatif dalam peribadahan melalui pendekatan komunitas keagamaan dalam era digital. Penelitian difokuskan pada Gereja Huria Kristen Batak Protestan (HKBP) Cilegon yang kesulitan mendapatkan akses mendirikan bangunan Gereja di Cilegon. Kehadiran pandemi Covid-19 memberikan momentum yang tepat untuk mengejewantahkan peribadahan online, mengingat sebagian besar Gereja telah melakukan ibadah secara online selama kurang lebih dua tahun. Rekomendasi yang dihasilkan adalah pendirian Gereja online yang melibatkan seluruh jemaat HKBP Cilegon dengan kepemimpinan yang diakui, legal, dan tercatat dalam Almanak HKBP. Jika dapat diaktifkan sesuai dengan aturan dan peraturan Gereja HKBP, ini akan menjadi Gereja online pertama di Indonesia. Penelitian ini menggunakan metode penelitian kualitatif dengan mengacu pada sumber berita online dan literatur pendukung.